2019
DOI: 10.21037/atm.2018.12.07
|View full text |Cite
|
Sign up to set email alerts
|

The profile of patients receiving public and private surgical services in Greece during the economic crisis: a comparative study

Abstract: Background: International experience has shown that deterioration of healthcare services is a common consequence of socioeconomic crises. Exact mechanism of this deterioration varies with respect to particularities of each healthcare system, government and administrative policies and local epidemiological conditions. The aim of the present study was to evaluate the effect of Greek economic crisis on the profile and the satisfaction rates of patients seeking surgical services in public and private hospitals. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Indeed, developing and promoting appropriate policies, guidelines, and regulations are necessary for the prevention of corruption and to manage the diagnostic and treatment choices of physicians [ 26 , 41 , 85 , 89 ]. A study in Greece showed that the economic crisis could shift the selection of the surgical technique toward less costly protocols [ 40 ]. On the other hand, a US study showed that doctors who had a closer tie to the hospital (e.g., employment) increased their treatment intensity, especially for patients with private insurance [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, developing and promoting appropriate policies, guidelines, and regulations are necessary for the prevention of corruption and to manage the diagnostic and treatment choices of physicians [ 26 , 41 , 85 , 89 ]. A study in Greece showed that the economic crisis could shift the selection of the surgical technique toward less costly protocols [ 40 ]. On the other hand, a US study showed that doctors who had a closer tie to the hospital (e.g., employment) increased their treatment intensity, especially for patients with private insurance [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…SNHI and distinctive craniofacial features are also cardinal features of PBDs. Nail abnormalities, including Beau lines and leukonychia, have been reported in patients with Heimler syndrome [ 46 , 51 , 53 , 54 , 55 ].…”
Section: Various Types Of Hhi Present With Cutaneous Abnormalitiesmentioning
confidence: 99%
“…For example, operating room utilization in the private healthcare system is perceived as more efficient compared to such in the public healthcare system. However, numerous studies have shown that the patient composition in those two systems is entirely different [14][15][16][17]. Compared with their counterparts in the public sector, patients receiving private elective surgeries are younger, have less comorbidities, and are from a higher socioeconomic class.…”
Section: Introductionmentioning
confidence: 99%